Cyber essentials for Nigerian business - Orunta, Nathaniel (2015)
In June 2014, the British government launched a scheme aimed at addressing the threat to cyber space in the UK. It sort to encourage Organisations to adopt good practice of information security, which includes framework and a simple technical security controls to protect information from threats associated with the internet. The scheme also ensures that a form of certification was necessary to demonstrate this. My research sorts to evaluate the extent in which organisations in Nigeria are aware of the requirement of cyber essentials and how far they have implemented these requirements. Nigeria having been ranked amongst the top 15 countries in the world noted for cybercrime from a survey found in a web site “balancing act- Africa.com” it become necessary that a survey be done using questionnaire addressed to some organisations banking, oil and gas and telecommunications industries. The result of the survey of the study indicate that although there is some level of awareness, only most of the companies with international link that responded to the questionnaires were aware of the prevalent cybercrime rate, and had implemented to a large extent recommended cyber essentials for businesses and industries. Others however are yet to show the same level of commitment in going for this or other standards. A number of discoveries were made, amongst others were: i. There is limited general awareness on what to do about cyber security which accounted for the majority of cybercrime. ii. There is no cyber security awareness program in place to sanitize organisations and small scale businesses, by various state and federal governments. iii. There is no kind of national security framework enacted by the various tier of government to combat cybercrime. iv. Insider aided security threats are as severe as those from outside. This makes it imperative that formal counter measures need to be put in place to discourage this trend. v. The lack of cyber security and control in the telecommunication sector made it easy for data acquisition of customer information through leakages, led to increased encouragement of cybercrime like phishing, identity theft and social engineering attacks etc.